Structure and properties of zinc 1,3-bdc metal-organic frameworks - Meekel, EG (2023)
Complexity in material design is widely recognised as a means of introducing unique properties that may be beneficial for various applications. The project described in this thesis aims to explore the efficiency of introducing such complexity into materials through the incorporation of low-symmetry components. Due to their ability of offering control over the geometry of building blocks, metal-organic frameworks (MOFs) were selected as the platform for this exploration.